A Pediatric Case of Kawasaki Disease with Gastrointestinal Involvement Mimicking Acute Abdomen - Patil, Prabhakar; Michael, Anwar Mousa (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Kawasaki Disease (KD) is a childhood acute vasculitis that predominantly affects medium-sized arteries, particularly the coronaries. While classical KD is diagnosed on the basis of defined clinical criteria, atypical presentations, such as with gastrointestinal (GI) involvement, can obscure timely recognition of this disease. GI symptoms, observed in subset of cases, may mimic acute surgical abdomen.Objective: To highlight the diagnostic challenge of Kawasaki Disease with predominant gastrointestinal symptoms mimicking acute abdomen in a pediatric case, and to emphasize the importance of early recognition and timely initiation of intravenous immunoglobulin (IVIG) therapy to prevent potential cardiac complications.Case: This is the case report of a 7-year-old male who was admitted with high-grade fever, severe abdominal pain, and signs suggestive of an acute abdomen. Initial clinical assessment and abdominal ultrasound indicated mesenteric lymphadenitis. Laboratory findings revealed marked leukocytosis, anemia, thrombocytosis, and elevated inflammatory markers (ESR, CRP) along with increased NT-proBNP suggestive of systemic inflammation. Further imaging ruled out surgical pathology. The persistence of fever, along with emerging mucocutaneous signs, led to the diagnosis of KD. The patient was treated with intravenous immunoglobulin (IVIG) and supportive therapy. Fever resolved within 24 hours, and abdominal symptoms improved markedly. Patient was then discharged afebrile with no evidence of coronary artery abnormalities on echocardiography.Conclusion: This case illustrates that persistent fever and elevated inflammatory markers in the presence of GI symptoms should prompt consideration of KD, even in the absence of full diagnostic criteria. Early diagnosis and IVIG therapy are important as delayed diagnosis may lead to significant cardiac sequelae.